Peran Penghindaran Pajak dalam Hubungan Karakteristik Perusahaan dan Nilai Perusahaan - Amrie Firmansyah; Nauval Muhammad; Ulfa Gita Rusmala (SUBSTANSI, 2021)
This study examines the effect of, leverage, profitability, and firm size on firm value. In addition, this study employs tax avoidance as a moderator. The research data consists of financial statements and share prices of energy sub-sector companies listed on the Indonesia Stock Exchange from 2016 to 2020. Data were obtained from www.idnfinancials.com, the company's official website, and www.finance.yahoo.com. Based on purposive sampling, the total sample used is 70 observations. Hypothesis testing is done by using multiple linear regression analysis for panel data. The test results show that profitability and firm size do not affect firm value, while leverage positively affects firm value. In addition, the interaction between tax avoidance and profitability affects firm value. Tax avoidance can also provide a moderating effect in the relationship between leverage and firm value, firm size and firm value.